2017
DOI: 10.1111/sltb.12428
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness as a Predictor of Suicide Ideation in Depressed Male and Female Adolescent Youth

Abstract: We examined hopelessness as a predictor of suicide ideation in depressed youth after acute medication treatment. A total of 158 depressed adolescents were administered the Children's Depression Rating Scale-Revised (CDRS-R) and Columbia Suicide Severity Rating Scale (C-SSRS) as part of a larger battery at baseline and at weekly visits across 6 weeks of acute fluoxetine treatment. The Beck Hopelessness Scale (BHS) was administered at baseline and week 6. A negative binomial regression model via a generalized es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 42 publications
1
51
0
1
Order By: Relevance
“…16 This findings is also consistent with Wolfe's research that indicates that hopelessness was positively related to suicidal ideation but is independent of a change in depression severity. 39 In addition, Anguiano 8 has found that hopelessness is more significant than depression in explaining suicidal ideation. Chochinov's 16 This indicates that demoralization could directly influence suicidal ideation, and it also has an indirect effect on suicidal ideation through depression.…”
Section: Correlations Among the Dimensions Of Hopelessness Demoralmentioning
confidence: 99%
“…16 This findings is also consistent with Wolfe's research that indicates that hopelessness was positively related to suicidal ideation but is independent of a change in depression severity. 39 In addition, Anguiano 8 has found that hopelessness is more significant than depression in explaining suicidal ideation. Chochinov's 16 This indicates that demoralization could directly influence suicidal ideation, and it also has an indirect effect on suicidal ideation through depression.…”
Section: Correlations Among the Dimensions Of Hopelessness Demoralmentioning
confidence: 99%
“…Hopelessness is a risk factor for suicidal ideation (Wolfe et al, 2017) and the indeterminate licence left some suicidal:
After 10 years you can apply for the licence to be taken off… If I don't come off, I might as well stick a gun in my mouth and pull the trigger. Because that's the only definite way to get off licence.
32, male, 3, 10
I'm always walking on eggshells, and there's no chance of me ever being free until I'm dead, whether that's through normal causes or cos I can't cope with it… IPP is hell and there's no end
53, male, 2, 4
…”
Section: Resultsmentioning
confidence: 99%
“…Finally, some potential confounders, such as family income, history of psychotropic medications, and familial mental health history were omitted. Hopelessness is a very important and independent risk factor for suicide, particularly amongst youth [ 78 ]. Future research is needed to replicate these findings in future.…”
Section: Discussionmentioning
confidence: 99%